2012
DOI: 10.1021/mp300043f
|View full text |Cite
|
Sign up to set email alerts
|

Partial Biodistribution and Pharmacokinetics of Isoniazid and Rifabutin Following Pulmonary Delivery of Inhalable Microparticles to Rhesus Macaques

Abstract: Dry powder inhalations (DPI) of microparticles containing isoniazid (INH) and rifabutin (RFB) are under preclinical development for use in pulmonary tuberculosis. Microparticles containing 0.25, 2.5, or 25 mg of each drug were administered daily for 90 days to rhesus macaques (n = 4/group). Single inhalations or intravenous (i.v.) doses were administered to separate groups. Drugs in serum, alveolar macrophages, and organ homogenates were assayed by high-performance liquid chromatography (HPLC). The RFB/INH in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The INH concentration in the MRI study, was based on published small animals studies, although the effectiveness of inhalable approach to INH-containing MPs administration has been proven in studies on large animals in vivo. Verma et al [61] have administered inhaled MPs containing INH to rhesus macaques in the following single dosages: 0.25, 2.5, and 25 mg. They observed that the intracellular INH concentration in alveolar macrophages was below limits for the lowest dose.…”
Section: Discussionmentioning
confidence: 99%
“…The INH concentration in the MRI study, was based on published small animals studies, although the effectiveness of inhalable approach to INH-containing MPs administration has been proven in studies on large animals in vivo. Verma et al [61] have administered inhaled MPs containing INH to rhesus macaques in the following single dosages: 0.25, 2.5, and 25 mg. They observed that the intracellular INH concentration in alveolar macrophages was below limits for the lowest dose.…”
Section: Discussionmentioning
confidence: 99%
“…This approach also resulted in higher drug concentrations in macrophages than oral, intra-cardiac injection and even intra-tracheal instillation of free drug solutions [5,88,89]. Inhalation of rifabutin and isoniazid loaded PLA microparticles by Rhesus macaques also evidenced an efficient targeting of alveolar macrophages and lung tissue sparing non-target sites such as blood, liver and kidneys from the toxic drugs [90]. The ability of rifabutin and isoniazid loaded PLA microparticles to sustain higher levels of drugs in the cytosol of macrophages and for longer periods in comparison with soluble drugs highlight their efficacy in stimulating innate biological responses evoking a bactericidal action including induction of free radicals, changes in membrane potential and apoptosis [91][92][93].…”
Section: Polylactide (Pla)mentioning
confidence: 99%
“…A considerable database is thus accumulating of novel formulations for drugs alone and in combination to treat pulmonary TB . Several of these papers go beyond formulation and present pharmacokinetic and/or tissue and bronchoalveolar lavage fluid data, indicating that therapeutic doses can be delivered as aerosols to the lungs . These doses may differ depending on the use of this route as a stand‐alone or an adjunct therapy with respect to a particular drug.…”
Section: Introductionmentioning
confidence: 99%
“…7,[25][26][27][28][29][30][31][32] Several of these papers go beyond formulation and present pharmacokinetic and/or tissue and bronchoalveolar lavage fluid data, indicating that therapeutic doses can be delivered as aerosols to the lungs. 11,15,[33][34][35][36] These doses may differ depending on the use of this route as a stand-alone or an adjunct therapy with respect to a particular drug. Recognizing that monotherapy is not an option in TB treatment, inhaled formulations may either contain more than one drug if they are to stand alone or may be combined with peroral administration of additional drugs.…”
Section: Introductionmentioning
confidence: 99%